Robust Finite-Time Tracking Control Based on Disturbance Observer for an Uncertain Quadrotor under External Disturbances - Hamid Hassani; Anass Mansouri; Ali Ahaitouf (Journal of Robotics)
In this paper, a robust flight control system is proposed for an autonomous quadrotor to quickly and accurately achieve the targeted trajectories. A novel supertwisting nonsingular terminal sliding mode control (STNTSMC) has been developed to ensure that the tracking errors vanish in a short finite-time. A nonlinear disturbance observer (DO) is incorporated into the control system to estimate the unknown external perturbations and to strengthen the system’s robustness. The Lyapunov theory is used to verify the closed-loop stability of the synthesized controller. Moreover, processor-in-the-loop (PIL) implementations are performed to validate the efficacy of the suggested method. The merit of the proposed DO-STNTSMC is evaluated under multiple flight scenarios. The obtained results demonstrate that the proposed controller has a highly reduced tracking error and strong robustness against random parameter changes and external disturbances, compared to conventional nonsingular terminal sliding mode control. Finally, experimental tests are conducted to validate the performance of the suggested method.